Catalytic reduction of amides to amines by electrophilic phosphonium cations via FLP hydrosilylation. Issue 82 (23rd September 2016) - Augurusa, Alessandra; Mehta, Meera; Perez, Manuel; Zhu, Jiangtao; Stephan, Douglas W.
Abstract : A catalytic methodology for the conversion of amides to amines is reported. Among the 25 examples, 14 reduce N -trifluoroacetamides to give trifluoroethylamines. Abstract : A catalytic methodology for the conversion of amides to amines is reported. Of the 25 examples described, 14 examples involve the reduction of N -trifluoroacetamides to the corresponding trifluoroethylamines. These reductions are achieved by catalytic hydrosilylation of the amide mediated by an electrophilic phosphonium cation (EPC) catalyst.